Perancangan Fasilitas Duduk Berbahan Rotan dengan Inovasi Flatpack - Yohanes Kevin Pratama; Adi Santosa; Grace Setiati Kattu (Intra, 2019)
The development of rattan industry currently has considerable opportunities. However, competitions between producers are also quite tight. Indonesia as the largest rattan supplier should have a wider opportunity to develop rattan products and be able to compete with industries in the market, especially international markets. This design is the development of rattan construction, namely flatpack construction. With this system, Indonesia’s rattan products are expected to be more competitive and developing. The method used are understanding rattan characters, understanding rattan construction, deepening design, making prototypes and branding. Products designed are lounge chairs, chosen because they have a fairly high level of difficulty in construction.